Roses Exhibit Pathotype‐specific Resistance Responses to Powdery Mildew. Issue 2 (22nd August 2013) - Hosseini Moghaddam, Hossein; Dewitte, Angelo; Van Bockstaele, Erik; Van Huylenbroeck, Johan; Leus, Leen
Abstract Disease resistance is highly desired in roses. Especially in garden rose breeding, efforts are being made to select for plants with raised levels of resistance towards powdery mildew. Despite the description of different pathotypes of powdery mildew and the development of pathotype‐specific QTLs, pathotype‐specific virulence and resistance mechanisms are not well known. To understand resistance in roses, different evaluation methods were used: disease scoring on inoculated detached leaves, evaluation of conidia development and plant responses by cell reactions. In this study, two rose genotypes, Rosa wichurana and Rosa 'Yesterday', were found to react differently towards two powdery mildew pathotypes (R‐E and R‐P). Although susceptible to R‐P, 'Yesterday' showed immunity to R‐E by arresting fungal development after conidium germination. Rosa wichurana showed partial resistance to pathotype R‐P and was even more resistant to pathotype R‐E by means of increasing amounts of cell reactions. Hybridization of 'Yesterday' × R. wichurana resulted in a diploid F1 population (90 genotypes). This population was screened for resistance mechanism–specific segregation to both fungal pathotypes. The results of both pathotypes exhibited a wide variation in resistance among the F1 genotypes. Our results showed that resistance reactions to powdery mildew in roses do not only result in different resistance mechanisms depending on the rose genotype but were also pathotype dependent.